A high-performance supercapacitor electrode material based on NiS/Ni3S4 composite. (1st March 2017) - Gou, Jianxia; Xie, Shengli; Yang, Zhichao; Liu, Yaqing; Chen, Yinjuan; Liu, Yanru; Liu, Chenguang
Highlights: Phase composition and particle size in nickel sulfides are engineered. Effects of phase composition and particle size on supercapacitive property are identified. The optimal NiS/Ni3 S4 composite electrode shows enhanced circling stability. Abstract: In this work, nickel sulfides were prepared via a facile hydrothermal method. The particle size and phase composition were tuned by the reaction temperature. Phase-property relationship of NiS/Ni3 S4 was established through combining characterization analysis with electrochemical tests. With the favorable particle size and composition, the NiS/Ni3 S4 composite delivered preferable gravimetric capacity (194.4 mAh g −1 at 2 A g −1, and 133.1 mAh g −1 at 10 A g −1 ) and impressive circling stability (89.5 mAh g −1 at 10 A g −1 after 5000 cycles).